2011
DOI: 10.1016/j.bbrc.2010.12.121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interactions between LPS transport proteins of the Lpt system

Abstract: The lipopolysaccharide transport system (Lpt) in Gram-negative bacteria is responsible for transporting lipopolysaccharide (LPS) from the cytoplasmic surface of the inner membrane, where it is assembled, across the inner membrane, periplasm and outer membrane, to the surface where it is then inserted in the outer leaflet of the asymmetric lipid bilayer. The Lpt system consists of seven known LPS transport proteins (LptA-G) spanning from the cytoplasm to the cell surface. We have shown that the periplasmic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
1
31
1
Order By: Relevance
“…LPS can be transferred from LptC to its structural homolog LptA, but not vice versa, consistent with the expected directionality in the LPS transport pathway (18). LptA was shown to bind to LptC (42, 43) but not to LptE (42), which would be consistent with the idea that LptE is not the LPS recipient at the OM. A more likely recipient for LPS could be the N terminus of LptD because it shows sequence similarity to LptA (6).…”
Section: Discussionsupporting
confidence: 77%
“…LPS can be transferred from LptC to its structural homolog LptA, but not vice versa, consistent with the expected directionality in the LPS transport pathway (18). LptA was shown to bind to LptC (42, 43) but not to LptE (42), which would be consistent with the idea that LptE is not the LPS recipient at the OM. A more likely recipient for LPS could be the N terminus of LptD because it shows sequence similarity to LptA (6).…”
Section: Discussionsupporting
confidence: 77%
“…The current model of LPS transport posits that LptBFG, which constitute an ABC transporter, extract LPS from the IM (5,(7)(8)(9)(10)(11), and then the molecule is passed to the periplasmic domain of LptC (8,(10)(11)(12). Next, additional ATP hydrolysis by LptBFG facilitates passage of LPS from LptC to LptA in the periplasm (6,(11)(12)(13). Multiple LptA proteins polymerize in end-on-end fashion to span the periplasm, from the IM LptBCFG components to the OM LptDE complex (14)(15)(16).…”
mentioning
confidence: 99%
“…Moreover, an intermolecular interaction that LptA can be co-purified with overexpressed LptC has already been established [17], and the two proteins can be stably associated when purified separately [12]. Recent studies showed that LptA interacts with the C-terminal part of LptC at the IM and the N-terminal part of LptD at the OM in vivo [13].…”
Section: Lpta Interacts With Both Im and Om Lpt Complexmentioning
confidence: 99%
“…However, its function is not well understood within the complex LptBFGC [5,[9][10][11]. LptA was proposed to act as a periplasmic chaperone for LPS transport across the periplasm and reported to interact with IM protein LptC [12,13] and OM protein LptD [13]. LptD and LptE form a stable complex at the OM which is proposed to serve as a translocon that facilitates the passage of LPS across the OM bilayer [14].…”
Section: Introductionmentioning
confidence: 99%